2020
DOI: 10.1177/2053168020966874
|View full text |Cite
|
Sign up to set email alerts
|

Public attitudes about emergent issues in LGBTQ rights: Conversion therapy and religious refusals

Abstract: Following legal recognition of marriages for same-sex couples, new topics have emerged in debates over LGBT rights. While numerous studies of public opinion about gay and transgender rights have been examined, some emergent issues remain underexamined. Two prominent issues are conversion therapy and denials of service based on religious beliefs in a variety of settings. These areas of LGBT rights are dynamic, with some states recently banning conversion therapy on minors, the Trump Administration’s guidance on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Consequently, there is a need to better understand the role of urbanicity in shaping support for LGBT rights. The limited evidence in from extant literature suggests that we might observe a general, positive relationship between residence in urban environments and support for LGBT rights (Flores et al 2020). My first hypotheses therefore provides a direct test of this relationship: H1: Support for LGBT rights is higher in urban environments than nonurban environments.…”
Section: Hypothesesmentioning
confidence: 90%
See 2 more Smart Citations
“…Consequently, there is a need to better understand the role of urbanicity in shaping support for LGBT rights. The limited evidence in from extant literature suggests that we might observe a general, positive relationship between residence in urban environments and support for LGBT rights (Flores et al 2020). My first hypotheses therefore provides a direct test of this relationship: H1: Support for LGBT rights is higher in urban environments than nonurban environments.…”
Section: Hypothesesmentioning
confidence: 90%
“…However, little attention has been paid to variation in support for LGBT rights across the urban-rural interface. Though some contemporary studies include a dichotomous measure of subjective urbanicity (Flores et al 2020), 2 many do not include one at all (Cao & Gurcay 2021, Castle 2019, Flores 2015, Flores, Haider-Markel, Lewis, Miller, Tadlock & Taylor 2018, Jones, Brewer, Young, Lambe & Hoffman 2018, Lewis, Tadlock, Flores, Haider-Markel, Miller & Taylor 2021.…”
Section: Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…In Ryan et al’s [ 8 ] sample, respondents who were not born in the US were more likely than those born in the US to report having been taken to a therapist or religious leader by their parents to change their SO. Hypothesizing the role of more conservative values, Flores et al [ 16 ] found lower support for banning conversion therapy among US racial and cultural minority groups. This conclusion supports the finding that ethnic minority parents report greater levels of homonegativity than ethnic majority parents [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…5 At present, those in the medical field have become more accepting of LGBTQ patients, advocating for equity and justice in patient care, with discrimination debated on a societal level, as evidenced by the federal government rescinding antidiscrimination protections for transgender Americans and the continued practice of conversion therapy for LGBTQ youth in a number of states. 6,7 It is important to recognize that discrimination against LGBTQ individuals is still occurring in the medical field, often systemically and without intention, and remains a major barrier to these patients seeking medical care. 8 Diversity, equity, and inclusion work in healthcare will benefit, not only patients, but also providers, fostering differences in ideas and further collaboration and growth.…”
mentioning
confidence: 99%